A companion to women in the ancient world - James, Sharon L.; James, Sharon L.; Dillon, Sheila; Dillon, Sheila (Blackwell companions to the ancient world, 2012)
Selected by Choice as a 2013 Outstanding Academic TitleAwarded a 2013 PROSE Honorable Mention as a Single Volume Reference/Humanities & Social SciencesA Companion to Women in the Ancient World presents an interdisciplinary, methodologically-based collection of newly-commissioned essays from prominent scholars on the study of women in the ancient world.The first interdisciplinary, methodologically-based collection of readings to address the study of women in the ancient worldExplores a broad range of topics relating to women in antiquity